Family-centered music therapy: empowering premature infants and their primary caregivers through music : results of a pilot study - Menke, Barbara M.; Haß, Joachim; Diener, Carsten; Pöschl, Johannes (PLOS ONE, 2021)
Background In Neonatal Intensive Care Units (NICUs) premature infants are exposed to various acoustic, environmental and emotional stressors which have a negative impact on their development and the mental health of their parents. Family-centred music therapy bears the potential to positively influence these stressors. The few existing studies indicate that interactive live-improvised music therapy interventions both reduce parental stress factors and support preterm infants’ development. Methods The present randomized controlled longitudinal study (RCT) with very low and extremely low birth weight infants (born <30+0 weeks of gestation) and their parents analyzed the influence of music therapy on both the physiological development of premature infants and parental stress factors. In addition, possible interrelations between infant development and parental stress were explored. 65 parent-infant-pairs were enrolled in the study. The treatment group received music therapy twice a week from the 21st day of life till discharge from hospital. The control group received treatment as usual. Results Compared to the control group, infants in the treatment group showed a 11.1 days shortening of caffeine therapy, 12.1 days shortening of nasogastric/ orogastric tube feed and 15.5 days shortening of hospitalization, on average. While these differences were not statistically significant, a factor-analytical compound measure of all three therapy durations was. From pre-to-post-intervention, parents showed a significant reduction in stress factors. However, there were no differences between control and treatment group. A regression analysis showed links between parental stress factors and physiological development of the infants. Conclusion This pilot study suggests that a live-improvised interactive music therapy intervention for extremely and very preterm infants and their parents may have a beneficial effect on the therapy duration needed for premature infants before discharge from hospital is possible. The study identified components of the original physiological variables of the infants as appropriate endpoints and suggested a slight change in study design to capture possible effects of music therapy on infants’ development as well. Further studies should assess both short-term and long-term effects on premature infants as well as on maternal and paternal health outcomes, to determine whether a family-centered music therapy, actually experienced as an added value to developmental care, should be part of routine care at the NICU.